Exploring the association between caffeine intake and benign prostatic hyperplasia: results from the NHANES 2005–2008 - Zhang, Fei; Zhang, Andong; Tao, Junyue; Zhang, Meng; Liang, Chaozhao (Frontiers in Nutrition, 2025)
BackgroundCoffee is a physiologically active food component prevalent throughout the world, but the association between caffeine intake and benign prostatic hyperplasia (BPH) has been limited in extensive epidemiological studies.MethodsWe conducted a cross-sectional study to evaluate the association between caffeine intake and BPH in adults in the United States using data from the National Health and Nutrition Examination Survey (NHANES) 2005–2008. Caffeine intake (mg/day) was evaluated based on a 24-h dietary recall. Multivariate logistic regression was used to analyze the independent relationship between caffeine intake and BPH, and the results are presented as odds ratio (OR) and 95% confidence interval (CI), subgroup analysis was also performed.ResultsA total of 2,374 participants were analyzed. After fully adjusting for potential confounders, logistic regression analysis revealed that higher caffeine intake was associated with a greater risk of BPH (ORT3vs1 = 1.52, 95% CI: 1.01–2.27; p = 0.04). In addition, this relationship was consistently observed across different subgroups, including individuals with lower education levels, a poverty income ratio (PIR) of 1.5 to 3.5, former smokers, married/living with partner individuals, those with uric acid levels of 5.5 to 6.5 mg/dL, those with hypertension, and those without cardiovascular disease (CVD).ConclusionThis study is the first to find a positive correlation between caffeine intake and BPH, but further research is needed to determine the exact causal relationship between these factors.